2017
DOI: 10.1186/s13014-017-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of proximal esophageal cancer after definitive combined chemo-radiation: a Swiss multicenter retrospective study

Abstract: ObjectiveTo report oncological outcomes and toxicity rates, of definitive platin-based chemoradiadiationtherapy (CRT) in the management of proximal esophageal cancer.MethodsWe retrospectively reviewed the medical records of patients with cT1-4 cN0-3 cM0 cervical esophageal cancer (CEC) (defined as tumors located below the inferior border of the cricoid cartilage, down to 22 cm from the incisors) treated between 2004 and 2013 with platin–based definitive CRT in four Swiss institutions. Acute and chronic toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…To the best of our knowledge, this is the largest study comparing Cis-versus CP-based CRT, with RT dose-escalation regimens in patients with proximal EC in a curative treatment approach. OS data in our cohort is consistent with results of previous observational studies in cervical or proximal EC exploring the effects of CRT, with 3-year OS rates of about 35-45% [33][34][35][36][37][38][39]. Recently, a small retrospective single institutional Korean study exploring the impact of radiation dose escalation on OS showed more favorable 3-year OS rates compared to the results in the current study, with 58% in the high-dose RT (59.4 Gy) and 49% of patients in the low-dose RT group (<59.4 Gy, p ¼ .69) [40].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, this is the largest study comparing Cis-versus CP-based CRT, with RT dose-escalation regimens in patients with proximal EC in a curative treatment approach. OS data in our cohort is consistent with results of previous observational studies in cervical or proximal EC exploring the effects of CRT, with 3-year OS rates of about 35-45% [33][34][35][36][37][38][39]. Recently, a small retrospective single institutional Korean study exploring the impact of radiation dose escalation on OS showed more favorable 3-year OS rates compared to the results in the current study, with 58% in the high-dose RT (59.4 Gy) and 49% of patients in the low-dose RT group (<59.4 Gy, p ¼ .69) [40].…”
Section: Discussionsupporting
confidence: 91%
“…Radiotherapy is a definitive treatment for cervical esophageal squamous cell carcinoma (CESCC). The total doses of definitive radiotherapy for CESCC range from 50 to 70 Gy [ 1 10 ]. Chemotherapy was concurrently administered in 28%–100% of patients [ 1 5 , 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with proximal esophageal tumors are usually poor candidates for surgery because of limitations in surgical techniques (e.g., confined working space and poor overview) . Furthermore, due to its anatomical proximity to the hypopharynx, surgery includes a combined pharyngo‐laryngo‐esophagectomy in some cases, resulting in permanent tracheostomy and affecting the quality of life of these patients enormously . Thus, these patients frequently depend on definitive chemoradiotherapy with encouraging 3‐year outcomes and acceptable toxicity …”
Section: Patient Selection For Surgerymentioning
confidence: 99%
“…12 Furthermore, due to its anatomical proximity to the hypopharynx, surgery includes a combined pharyngo-laryngo-esophagectomy in some cases, resulting in permanent tracheostomy and affecting the quality of life of these patients enormously. 13 Thus, these patients frequently depend on definitive chemoradiotherapy with encouraging 3-year outcomes and acceptable toxicity. 13 Comorbidity Accurate patient selection for surgery does not only depend on tumor characteristics, but also on assessment of comorbidities, patient nutritional status, and cardiopulmonary function.…”
Section: Patient Selection For Surgerymentioning
confidence: 99%
See 1 more Smart Citation